PENGARUH POLA ASUH ORANGTUA TERHADAP PEMBENTUKAN KARAKTER ANAK DI ZAMAN GENERASI STRAWBERRY - Afrilya Herianty; Arri Handayani; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research investigates the influence of parenting styles on the formation of children's character in the era of the Strawberry Generation. The Strawberry Generation refers to a group of young people considered more susceptible to emotional stress and lacking resilience in facing life challenges. In this context, the role of parenting styles becomes a determining factor in shaping children’s character. The study was conducted through literature reviews. The analysis that shaped the results of this research is expected to provide a profound understanding of the relationship between parenting styles and children’s character in the context of the Strawberry Generation era. The findings of this research can guide parents, educators, and practitioners in developing more effective parenting strategies to assist in the formation of children's character. Moreover, this research contributes to our understanding of the factors shaping the specific characteristics of the younger generation in this turbulent era